Community Empowerment Through Village Deliberation In RPJMDES 2025 Formulation In Lempangang Village - Ibnu Imam Al Ayyubi; Nurhikmah; Eko Prayetno; Firda Noerzanah; Tovi Primaresty (Ponpes As-Salafiyyah Asy-Syafi'iyyah, 2026)
This study discusses the implementation of Village Deliberation in the discussion and determination of the 2025 Village Medium-Term Development Plan (RPJMDES) in Lempangang Village. RPJMDES is a village development planning document prepared for a period of six years, aimed at determining the direction of village development in accordance with community aspirations and local needs. This study uses a qualitative descriptive approach, with data collection techniques including in-depth interviews with 12 key informants, participatory observation, and documentation. The results of the study indicate that the Village Deliberation in Lempangang Village was carried out with a good level of community participation, with over 60% attendance of village residents during the deliberation meetings, although community understanding of the technical aspects of planning still needs to be improved. The village government and the Village Consultative Body (BPD) play a central role in facilitating the deliberation, while decision-making is carried out in a deliberative manner through consensus. This planning process is also aligned with national and regional development programs to optimize external support. Constraints faced in the preparation of RPJMDES include limited budget, resources, and coordination between parties. This study recommends increasing community capacity in development planning, strengthening synergy between the village government and BPD, and optimizing local resources. In conclusion, the Village Deliberation in Lempangang Village has created a strong foundation for inclusive and sustainable village development planning.